2015
DOI: 10.3732/ajb.1400484
|View full text |Cite
|
Sign up to set email alerts
|

Testing the SI × SC rule: Pollen–pistil interactions in interspecific crosses between members of the tomato clade (Solanum section Lycopersicon, Solanaceae)

Abstract: The SI × SC rule explains many of the compatibility relations in the tomato clade, but exceptions occur with more recently evolved SC species and accessions, revealing differences in strength of both pistil and pollen IRBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
160
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(173 citation statements)
references
References 55 publications
12
160
0
1
Order By: Relevance
“…Two wild relatives of cultivated tomato, S. cheesmaniae and S. galapagense, both SC, also lack an SLF-23 ortholog, and their pollen is also rejected on pistils of SI species (16,18). These taxa also lack functional ui6.1 (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two wild relatives of cultivated tomato, S. cheesmaniae and S. galapagense, both SC, also lack an SLF-23 ortholog, and their pollen is also rejected on pistils of SI species (16,18). These taxa also lack functional ui6.1 (21).…”
Section: Discussionmentioning
confidence: 99%
“…Three other red-or orange-fruited species, S. cheesmaniae, S. galapagense, and S. pimpinellifolium, are bilaterally cross-compatible with each other and with S. lycopersicum. There are notable exceptions to SI × SC rule in the tomato clade (18). One is that pollen of all of the red/ orange-fruited species (SC) are rejected on pistils of the SC greenfruited species.…”
mentioning
confidence: 99%
“…They noted that this so-called SI 3 SC rule applies to many crosses in the Solanaceae and Scrophulariaceae (McGuire and Rick, 1954) and suggested that it was regulated by the S-locus (Lewis and Crowe, 1958). A recent comprehensive study of interspecific compatibility in the tomato clade demonstrated that the SI 3 SC rule is closely followed at the species level (Baek et al, 2015). In addition to the Solanaceae, UI consistent with the SI 3 SC rule has been recorded in Lilliaceae (Ascher and Peloquin, 1968), Poaceae (Heslop-Harrison, 1982), Brassicaceae (Sampson, 1962;Hiscock and Dickinson, 1993), and Orchidaceae (Pinheiro et al, 2015).…”
Section: Si and Interspecific Incompatibility: A Common Toolkitmentioning
confidence: 99%
“…Right, SI S. chilense LA2884 pollinated by S. lycopersicum 'VF36'. The UI rejection response in this example occurs closer to the stigma and is typical of crosses between SI green-fruited species and SC red-fruited species (Baek et al, 2015). Arrows indicate the position in the style where fewer than three pollen tubes pass at 48 h after pollination (compatible pollen tubes reach the ovary after 24 h).…”
Section: S-rnase-based Simentioning
confidence: 99%
See 1 more Smart Citation